JURIDICAL ANALYSIS OF IMPLEMENTATION OF INVESTIGATIONS ON THE CRIMINAL ACTION OF ABUSE AND OR ABILITY OF CHILDREN - Edy Siswanto; Yuda Sudawan (JILPR Journal Indonesia Law and Policy Review, 2023)
The crime of obscenity is part of the crime against decency. This obscenity does not only happen to adults but also to minors. In this research, the type of research used is normative legal research/normative juridical research. The results of the study show that the process of investigating criminal acts of sexual abuse and/or intercourse with children is carried out in several stages, namely making reports, conducting investigations, conducting visum et refertum (VeR), conducting cases, sending notices of commencement of investigations, examining witnesses, conducting case titles determining suspects, arresting suspects, conducting examinations of suspects, collecting evidence and conducting filings. The inhibiting factors in the investigation of criminal acts of sexual abuse and/or intercourse with children are obtained from internal and external factors, internal factors include the knowledge of investigators, difficulty obtaining visum et repertum, difficulty in presenting witnesses and suspects running away. While external factors include facilities or facilities that support law enforcement and community environmental factors.